Peran Teknologi Informasi dan Komunikasi pada Pembelajaran Daring di Masa Pandemi Covid-19 - Nadya Isradini dkk (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
This research is a qualitative descriptive study that aims to determine the role of information and communication technology in the online learning process during the Covid-19 Pandemic. The data collection technique was done by using triangulation techniques, namely observation, interviews, and documentation to the same source, namely teachers and parents of students. Based on research that has been conducted at SD Qur'an Al-Himmah, Sukabumi Regency, it can be concluded that information and communication technology acts as a teacher media to deliver learning material, as a medium of communication, and consultation between teachers and students or parents of students, and as a teacher media, students and parents to add insight from the internet. Popular media (applications) used by teachers and students at SD Qur'an Al-Himmah in the online learning process are the WhatsApp Group application, Zoom Cloud Meeting, and YouTube. The problems (obstacles) faced by teachers and parents of students in the online learning process are bad signals that hinder the online learning process, increasing quota costs, decreasing interest in children's learning, and limited time to accompany children because parents have to work around the clock. At the same time.